Pediatric population (aged 3-11 years) received primary inactivated SARS-CoV-2 vaccination prior to infection exhibiting robust humoral immune response following infected with Omicron variant: a study conducted in Beijing - Li, Jing; Li, Jingjing; Dai, Shuzhi; Dang, Li; Wang, Lin; Cao, Ling; Chen, Xiaobo; Wang, Ying; Ge, Menglei; Liu, Weijie; Song, Qinwei; Xu, Wenjian; et al. (Frontiers in Immunology, 2023)
Objective Analysis of SARS-CoV-2 IgG antibody and neutralizing antibody levels following SARS-CoV-2 infection in children aged 3-11 years, comparing those who had received the inactivated SARS-CoV-2 vaccine to those who were unvaccinated prior to infection, provides evidence for public health centers in formulating vaccination strategies and control policies. Methods A study was conducted on children who visited the Children’s Hospital, Capital Institute of Pediatrics from January 10, 2023 to March 31, 2023 (Beijing, China). Participants or their guardians completed a survey questionnaire providing information about their SARS-CoV-2 infection history and vaccination status. Serum samples were collected for testing of SARS-CoV-2 immunoglobulin G (IgG) and neutralizing antibodies (Nabs), which were performed using chemiluminescence immunoassay. Results The study included 1,504 children aged 3-11 years with previous SARS-CoV-2 infection history. Among the 333 unvaccinated children, the serum SARS-CoV-2 IgG antibody level was median 2.30 (IQR, 1.27-3.99). However, children received one dose (78 cases) and two doses (1093 cases) of the inactivated vaccine prior to infection showed significantly higher SARS-CoV-2 IgG antibody levels, with values of median 10.11 (IQR, 8.66-10.93) and median 10.58 (IQR, 9.79-11.07), respectively. As to the unvaccinated children, 70.3% (234/333) were negative for SARS-CoV-2 Nabs, which were less than 6.00AU/ml. The remaining 29.7% (99/333) showed relatively low levels of Nabs, ranging from 6.00 to 50.00AU/ml. In contrast, for children who had received two doses of vaccine prior to infection, an overwhelming 99.3% (1086/1093) exhibited high levels of Nas in the range of 100.00-120.00 AU/ml. Remarkably, these elevated Nab levels persisted for at least a period of 3 months post-infection in children who had received two doses of inactivated SARS-CoV-2 vaccine prior to infection, regardless of age or sex and vaccine manufacturer. Conclusion The administration of two doses of inactivated SARS-CoV-2 vaccine prior to infection has been shown to significantly enhance humoral immunity following SARS-CoV-2 infection in pediatric populations, producing adequate Nabs that persist at elevated levels for up to 3 months post-infection. For unvaccinated children who displayed weak humoral immunity following a primary natural infection, timely vaccination is recommended to bolster their immunization protection. The findings underscore the importance of vaccination in strengthening immune responses and protecting pediatric populations against SARS-CoV-2 infection.